Humanistic approaches as the basis of the student clausura concept - Gryaznova, Nadezhda (project baikal, 2026)
The article examines the control clausuras made by the 2nd-year students of the Moscow Architectural Institute, from the standpoint of the professional skills they have acquired. The formation of the proposed architectural concepts is analyzed, both basing on the developed spatial and artistic solutions, and relying on the moral and humanitarian attitudes of future architects
Keywords: clausura; concept; project; spatial solution; artistic solution; social position